Efektivitas Pelayanan Perekaman E-KTP pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Boalemo - Alfazrin Hela; Arifin Tahir; Yacob Noho Nani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to examine how time, accuracy, and service delivery style affect the effectiveness of E-KTP registration services at the Population and Civil Registration Office of Boalemo Regency. The study employed a qualitative methodology with techniques of data collection, including interviews, observation, and documentation. Data analysis was then conducted through data reduction, data display, and conclusion drawing. The findings indicate that the effectiveness of E-KTP registration services at the Population and Civil Registration Office of Boalemo Regency is determined as satisfactory. However, considering the time, accuracy, and service delivery style, it is not yet optimal. Among the factors studied, time and accuracy are identified as suboptimal. Time is influenced by equipment readiness and staff capacity, with challenges such as network issues and equipment malfunctions affecting service duration. Meanwhile, accuracy is generally adequate, however, technical errors in data input and verification persist, primarily due to insufficient re-verification by staff. This suggests that implementing, accuracy in E-KTP registration services remains less than optimal.